Hadith #1882 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Zayd ibn Aslam that the Messenger of Allah, may Allah bless him and grant him peace, said, “The one riding greets the one walking, and when one of a group of people gives a greeting, it is enough for all of them.”
Grade:

Hadith #1883 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Wahb ibn Kaysan that Muhammad ibn Amr ibn Ata said, “I was sitting with Abdullah ibn Abbas when a Yemeni man came in. He said, ‘Peace be upon you, and the mercy of Allah and His blessing’ (as-salamu alaykum wa rahmatullahi wa barakatuhu), and then he added something more to that. Ibn Abbas said (and at that time his eyesight had gone), ‘Who is this?’ People said, ‘This is a Yemeni who has come to see you,’ and they introduced him. Ibn Abbas said,
Grade:

Hadith #1884 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Abdullah ibn Dinar that Abdullah ibn Umar said that the Messenger of Allah, may Allah bless him and grant him peace, said, “When a jew greets you, and says ‘Death to you’ (as-samu alaykum) say, ‘And to you.’ ” Yahya said, “Malik was asked whether a person who greeted a jew or christian, should apologise for it. He said, ‘No’.”
Grade:

Hadith #1885 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Ishaq ibn Abdullah ibn Abi Talha from Abu Murra, the mawla of Aqil ibn Abi Talib from Abu Waqid al-Laythi that the Messenger of Allah, may Allah bless him and grant him peace, was sitting in the mosque with some people when three people came in. Two came toward the Messenger of Allah, may Allah bless him and grant him peace, and one went away. When the two stopped at the assembly of the Messenger of Allah, may Allah bless him and grant him peace, they gave the
Grade:

Hadith #1886 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Ishaq ibn Abdullah ibn Abi Talha that Anas ibn Malik heard Umar ibn al-Khattab return the greeting of a man who greeted him. Then Umar asked the man, “How are you?” He said, “I praise Allah to you.” (Ahmadu ilayka Allah) Umar said, “That is what I wanted from you.”
Grade:

Hadith #1887 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Ishaq ibn Abdullah ibn Abi Talha that at-Tufayl ibn Ubayy ibn Kab told him that he visited Abdullah ibn Umar one morning and went out with him to the market, and when they were out, Abdullah ibn Umar did not pass by anyone selling poor merchandise or selling commodities or a needy person or anyone but that he greeted them. At-Tufayl said, “I came to Abdullah ibn Umar one day and he asked me to follow him to the market. I said to him, ‘What will you do in t
Grade:

Hadith #1888 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik from Yahya ibn Said that a man greeted Abdullah ibn Umar. He said, “Peace be upon you and the mercy of Allah and his barakat, on and on.” Abdullah ibn Umar said to him, “And on you, a thousand times,” as if he disliked that.
Grade:

Hadith #1889 - Muwatta Malik (Muwatta Malik)
Yahya related to me from Malik that he heard that when one entered an unoccupied house, one should say, “Peace be upon us and on the slaves of Allah, who are salih.” (As-salamu alayna wa ala ibadillahi’s-saliheen).O
Grade: